2011
DOI: 10.2337/dc11-1155
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Incidence and Long-Term Exposure to Air Pollution

Abstract: OBJECTIVEdAnimal and cross-sectional epidemiological studies suggest a link between air pollution and diabetes, whereas the limited prospective data show mixed results. We studied the association between long-term exposure to traffic-related air pollution and incidence of diabetes.RESEARCH DESIGN AND METHODSdWe followed 57,053 participants of the Danish Diet, Cancer, and Health cohort in the Danish National Diabetes Register between baseline (1993-1997) and 27 June 2006. We estimated the mean levels of nitroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
184
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(205 citation statements)
references
References 28 publications
20
184
1
Order By: Relevance
“…One article reported two individual cohort studies, and was extracted as two individual studies (14). Thus, ten prospective cohort studies from nine articles were finally included into the meta-analysis (10,11,12,13,14,20,21,22,23). Table 1 shows the main characteristics of those ten cohort studies included in the meta-analysis (Table 1).…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…One article reported two individual cohort studies, and was extracted as two individual studies (14). Thus, ten prospective cohort studies from nine articles were finally included into the meta-analysis (10,11,12,13,14,20,21,22,23). Table 1 shows the main characteristics of those ten cohort studies included in the meta-analysis (Table 1).…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…Table 1 shows the main characteristics of those ten cohort studies included in the meta-analysis (Table 1). Those ten cohort studies involved a total of 2 371 907 participants and 21 095 incident cases of type 2 diabetes (10,11,12,13,14,20,21,22,23). Among those ten cohort studies, nine studies reported incident new cases of type 2 diabetes (10,11,13,14,20,21,22,23), while the left one reported events of deaths coded as diabetes (12).…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…2009; Farhat et al, 2011), central nervous system disorders (Sunderman, 2001;Kreyling et al, 2006;Block and Calderon-Garciduenas, 2009;Pearson et al, 2010;Wang et al, 2012) and diabetes (Andersen, 2012;Andersen et al, 2012). Since many of these health conditions are interlinked, comprehensive studies are required to better understand the impact of PM 2.5 .…”
Section: Introductionmentioning
confidence: 99%